Peritoneal mesothelioma mortality in Italy: Spatial analysis and search for asbestos exposure sources. (June 2019) - Zona, A.; Fazzo, L.; Minelli, G.; De Santis, M.; Bruno, C.; Conti, S.; Comba, P.
Highlights: In Italy, 2003–2014, 747 recorded deaths for malignant peritoneal mesothelioma (0.10/100, 000). Mesothelioma annual mortality rates: 0.14/100, 000 in men, 0.07 in women. 4% of mesothelioma deaths in men and 6.15% in women are peritoneal mesotheliomas. In 364 municipalities significant excesses of mortality for MPeM. Five mortality significant clusters (p < 0.10) were detected. Abstract: Background: This study is part of a national plan of epidemiological surveillance of malignant mesothelioma (MM) mortality in Italy. The paper shows the results of malignant peritoneal mesothelioma (MPeM) mortality study in Italian Regions and municipalities. Methods: National Bureau of Statistics data for MPeM municipal mortality (ICD-10, Code C45.1) were analyzed in the time-window 2003–2014: mortality standardized rates (reference Italian population, census 2011), temporal trends of the annual national rates, Standardized Mortality Ratios and a municipal clustering analysis were performed. Results: 747 deaths for MPeM were recorded (0.10/100, 000): 464 in men (0.14/100, 000) and in 283 women (0.07/100, 000). No significant MPeM mortality temporal trend was found. Seventeen municipalities showed excesses of mortality for MPeM in at least one gender and/or overall population. Four clusters in male population, and one in women were identified. Conclusions: The study identifies some areas where remediation activities and/or health care actions may be warranted.